Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/atmos11040431
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Windstorms in the Lee of the Taebaek Mountains, South Korea: Characteristics and Generation Mechanisms

Abstract: The Yeongdong region, located east of the Taebaek Mountains, South Korea, often experiences severe windstorms in spring, causing a lot of damages, especially when forest fires spread out rapidly by strong winds. Here, the characteristics and generation mechanisms of the windstorms in the Yeongdong region on 8 April 2012 are examined through a high-resolution Weather Research and Forecasting (WRF) model simulation. In the Yangyang area, the steep descent of the isentropes on the lee slope of the mountain and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The occurrence of Type 1 (clusters 1, 2, and 5) was found to be dominant in the springtime when the moving synoptic high-and low-pressure systems were often observed. Consistently, previous studies (Jang & Chun, 2010;Kim & Chung, 2006;Lee et al, 2020) mentioned that this south-high and north-low pattern had often been observed when DWs occurred in the YD region in the springtime. Type 2 (clusters 3, 4, and 8) was found to mostly occur in the wintertime.…”
Section: Monthly Distributionsupporting
confidence: 88%
See 4 more Smart Citations
“…The occurrence of Type 1 (clusters 1, 2, and 5) was found to be dominant in the springtime when the moving synoptic high-and low-pressure systems were often observed. Consistently, previous studies (Jang & Chun, 2010;Kim & Chung, 2006;Lee et al, 2020) mentioned that this south-high and north-low pattern had often been observed when DWs occurred in the YD region in the springtime. Type 2 (clusters 3, 4, and 8) was found to mostly occur in the wintertime.…”
Section: Monthly Distributionsupporting
confidence: 88%
“…Accordingly, there were dense isobars across the Korean Peninsula between the high‐ and low‐pressure systems. This south‐high and north‐low pattern has often been mentioned in the previous studies as a typical synoptic SLP pattern that causes DWs in the YD region (Jang & Chun, 2010; Kim & Chung, 2006; Lee et al., 2020).…”
Section: Classified Synoptic Patternssupporting
confidence: 67%
See 3 more Smart Citations